Structural and functional impacts of amino acid substitutions that create blood group antigens: implications for immunogenicity. Issue 3 (5th February 2017) - Howe, John G.; Stack, Gary
Abstract : BACKGROUND: The immunogenicities of polypeptide blood group antigens vary widely. One possible determinant of immunogenicity is antigenic foreignness. The goal was to employ alternative ways of assessing foreignness and determine whether foreignness was related to immunogenicity. STUDY DESIGN AND METHODS: Foreignness was assessed as the extent of protein functional disruption caused by the exofacial amino acid (AA) substitutions that create blood group antigens, using AA substitution prediction algorithms such as Meta‐SNP and according to whether those substitutions were radical or conservative. RESULTS: AA substitutions that create the most immunogenic antigens had the highest Meta‐SNP scores, predictive of greater protein structure and function changes. Four of the 11 exofacial AAs that distinguish the most immunogenic antigen, RhD, from RhCE, and substitutions creating four of the five next most immunogenic antigens had the highest Meta‐SNP scores (0.293‐0.649). Excluding the outlier Jk a, the mean Meta‐SNP score of the four most immunogenic non‐RhD antigens (K, Lu a, E, c) was 3.7‐fold higher than the mean of the four least immunogenic (M, Fy a, C, S), 0.459 versus 0.123 (p = 0.0026). Regression analysis revealed a relationship between immunogenicity and Meta‐SNP score (R 2  = 0.953). Actual protein functional disruption was predicted for the AA substitution creating the E antigen. An AA cluster at Positions 350, 353, and 354 of RhD was unique, containing radical substitutions according to two classification schemes and relatively high Meta‐SNP scores (0.351‐0.432). CONCLUSION: The immunogenicity of blood group antigens was related to the functional disruption caused by the AA substitutions that create the antigens, as measured by Meta‐SNP score.